3D hierarchical porous CuS flower-dispersed CNT arrays on nickel foam as a binder-free electrode for supercapacitors. (26th June 2019) - Quan, Yiling; Zhang, Mingyuan; Wang, Guoxiang; Lu, Lu; Wang, Zhixin; Xu, Hongfeng; Liu, Sa; Min, Qingwang
Abstract : To fabricate excellent electrochemical supercapacitors, 3D porous copper sulfide flower dispersed carbon nanotube on nickel foam (CuS–CNTs@NF) with high energy density and stability were synthesized via a simple one-step solvothermal method. Abstract : To fabricate excellent property electrochemical supercapacitors (ECs), 3D hierarchical porous copper sulfide (CuS) flower-dispersed carbon nanotube (CNT) composites on nickel foam (CuS–CNTs@NF) with high energy density and good stability were synthesized via a simple one-step solvothermal method. The 2D CuS nanosheets and nanoflowers were chained together by 1D CNTs to form 3D CuS–CNT composites. The CuS–CNT composites with a cross-linking architecture provided a path that facilitated the rapid current response of electrolyte ions or electrons. Meanwhile, the MWCNTs as supporting materials can effectively prevent the self-curling of the CuS nanosheets. The CuS–CNT composites on nickel foam restricted the agglomeration of the CuS nanoflowers and afforded CuS–CNT composites with good stability during the charge or discharge process. The assembled CuS–CNTs@NF//AC asymmetric device exhibited large capacitance, high energy density (22.14 W h kg −1 ), and excellent cycling retention (86.01%) after 5000 cycles at 2 A g −1 .